Digital Memory Studies - Hoskins, Andrew, author.
1 online resource (328 pages)
Keywords: "Digital media, networks and archives reimagine and revitalize individual, social and cultural memory but they also ensnare it, bringing it under new forms of control. Understanding these paradoxical conditions of remembering and forgetting through today's technologies needs bold interdisciplinary interventions.Digital Memory Studies seizes this challenge and pioneers an agenda that interrogates concepts, theories and histories of media and memory studies, to map a holistic vision for the study of the digital remaking of memory. Through the lenses of connectivity, archaeology, economy, and archive, contributors illuminate the uses and abuses of the digital past via an array of media and topics, including television, videogames and social media, and memory institutions, network politics and the digital afterlife."--Provided by publisher.